2020
DOI: 10.1186/s13054-020-2841-7
|View full text |Cite
|
Sign up to set email alerts
|

Special attention to nurses’ protection during the COVID-19 epidemic

Abstract: As of March 8, 2020, the novel coronavirus disease 2019 (COVID-19) had caused 80,815 human infections and 3073 deaths in China, including more than 3000 infections among medical staff. Guangdong Second Provincial General Hospital (Guangzhou, Guangdong Province, China), a provincial emergency hospital, has treated more than 35 confirmed cases of COVID-19 and more than 260 suspected cases. Most of nurses' work involves direct contact with patients. As nurses have high vulnerability to COVID-19, it is necessary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
276
1
77

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(361 citation statements)
references
References 1 publication
7
276
1
77
Order By: Relevance
“…The fact that individuals infected with the COVID-19 virus experience respiratory difficulty and require intensive care necessitates that they should be treated in intensive care settings [7]. Healthcare providers are at high risk and it has been reported that more than 3,000 medical staff have been infected in China [8]. Anesthesiologists are in close contact with infected patients and are vulnerable in terms of exposure to respiratory droplets or aerosols from patients' airways.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that individuals infected with the COVID-19 virus experience respiratory difficulty and require intensive care necessitates that they should be treated in intensive care settings [7]. Healthcare providers are at high risk and it has been reported that more than 3,000 medical staff have been infected in China [8]. Anesthesiologists are in close contact with infected patients and are vulnerable in terms of exposure to respiratory droplets or aerosols from patients' airways.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses who involved in first line treatment of patients with COVID-19 received education and training on use of PPE and personal emotion management in some hospitals [11] . Meanwhile, the daily working time was restricted to avoid PPE-associated complications, such as dehydration, as described by us and the other study [11] . However, as described in this study, due to shortage of nurses in this pandemic, the proportion of nurses who had no experience to work in PPE before this pandemic in frontline of treating COVID-19 was higher than expected.…”
Section: Discussionmentioning
confidence: 99%
“…There were more than 3,000 health workers in China and at least 9,000 in US reported infected. [12,13] More than 40,000 health workers were infected in Europe according to local media. The importance of protecting health worker from high infection risk has been emphasized by many authors.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al recommended a working shift system of continuously working for six hours because working for longer duration made workers feel exhausted and even dizzy. [12] Thus, health workers involved in this study were divided into two groups according to different working duration (less than or over six hours) in isolation wards. No signi cant difference was observed between these two groups.…”
Section: Discussionmentioning
confidence: 99%